Enhanced Methane Adsorption Using Zeolite-A Derived from Coal Bottom Ash Supported with Activated Pineapple Leaf Fiber - Randy Yusuf Kurniawan; Dwi Miftha Kurnia; Martasari Beti Pangestuti; Efraim Eleizer Manurung; Taufik Qodar Romadiansyah (Jurnal Kimia Riset, 2026)
The present work evaluates the influence of mineral purification and zeolite formation from coal bottom ash (ZAB) on methane adsorption behavior, including the effect of incorporating KOH-treated pineapple leaf fibers as a supporting matrix (ZAB-X). ZAB was synthesized hydrothermally from Si and Al extracts from bottom ash through a smelting process at 650°C. Meanwhile, in the ZAB-X sample, pineapple leaf fibers were first activated by soaking in a 4 M KOH solution for 20 hours before being added to the zeolite slurry. Coal bottom ash was characterized using XRF and XRD to determine mineral content and phase, ICP-AES to determine the concentration of Si and Al extracts from the smelting results, while ZAB and ZAB-X solids were characterized using XRD and SEM to analyze morphology. The results of methane gas adsorption capacity under ambient conditions, specifically at 29 °C and under the applied pressure conditions, showed that ZAB-X had the highest capacity value of 7.75% by weight, followed by ZAB, BA after Fe and Ca Treatment, and BA, which were 4.69%, 2.34%, and 1.33%. The enhanced adsorption performance of ZAB-X was attributed to the formation of well-distributed zeolite crystals on the activated fiber surface, reduced particle agglomeration, and improved pore accessibility, which collectively promoted stronger methane confinement within the adsorbent structure. The obtained results indicate that aluminosilicate materials derived from industrial waste possess promising potential for sustainable methane capture applications.